Collusion between public procurers and suppliers in the context of japan's public procurement: The role of the risks of "unsuccessful procurement". Issue 3 (1st March 2016) - Tanaka, Satoru; Hayashi, Shuya
Abstract : This paper examines the economic forces which may lead to government-assisted or -facilitated bid-rigging (kansei-dango) in public procurement in Japan, and considers their implications. A public official may often worry about situations where his/her procurement project will not be successfully implemented. Based on a simplified theoretical treatment and on case studies of kansei-dango, it is argued that the desire to avert the risk of unsuccessful procurement resulting from the "experience goods" status of procured goods and/or services may be one reason for bid-rigging. Based on this understanding of kansei-dango, we discuss some implications for policies to restrain this type of corruption.